Distribution of Alloying Elements within the Constituent Phases of a C-containing Î³-TiAl Based Alloy studied by Atom Probe Tomography. Issue 1760 (2nd January 2015) - Baker, I.; Heilmaier, M.; Kishida, K.; Mills, M.; Miura, S.; Klein, Thomas; Mendez-Martin, Francisca; Schachermayer, Michael; Rashkova, Boryana; Clemens, Helmut; Mayer, Svea
ABSTRACT The distribution of alloying elements in the constituent phases of a C-containing Î³-TiAl based alloy has been characterized locally by atom probe tomography. The major elements of the alloy under consideration â€" Ti, Al, Nb, and Mo â€" are distributed uniformly within each of the constituent phases. Furthermore, Mo is preferentially dissolved in the Î²o-phase, whereas Nb content is similar in all phases. The selected C concentration of the alloy is below the overall solubility limit as no precipitates have been observed. Therefore, C is enriched in the Î±2-phase, whereas the Î²o-phase is depleted of C. In addition, Î²o/Î³-interfaces have been prepared by site specific sample preparation and characterized by atom probe tomography. Segregation of Mo and C into the interfaces and their close vicinity was observed.